A Review on modeling the channel potential in multi-gate MOSFETs - Hossein Mohammadi; Huda Abdullah; Chang, Fu Dee (Universiti Kebangsaan Malaysia, 2014)
This paper attempts to give a detailed review and provide a complete description on the technology, physics and modeling of various Multi-Gate MOSFETs. It consists of a synopsis of mathematical depiction of the potential distribution along the channel of various MG-MOSFETs which can be made to enable fast computer analysis of device behavior. This serves a link between process technology and circuit design. This review demonstrates that this technology is strongly desired in nanoscale domain and there is a plenty demand for analytical model which can explain the physics and operation of the devices perfectly.